Design and Development of an Educational Mobile Application to Optimize Communication and Interaction Between Members of Educational Institutions in Real Time - Ruiz Rivera, María Elena (2021)
The objective of this research is to optimize the communication and interaction between members of educational institutions, using a mobile application to improve service quality of the institution. By using the database with the information collected by the institution, as an important source for the integration and collection of education sector information, each institution is considered as an entity; it could be said that all the people who interact with it are the population, which needs to be connected and communicated with each other to subsist. Based on the exposed premises, a mobile application is designed to gather all users that interact with the same institution in a single platform. Thus, users are connected and communicated with each other by determining specific roles, which will have specific functions enabled for each type of user.